THE EVOLUTION OF THE JOURNAL ENTRY. - Littleton, A. C. (The Accounting Review, 1928)
Abstract The journal entry is all important bookkeeping mechanism which serves as a means of converting a non-technical statement of a transaction into a species of technically-formed, intermediate statistical record. It is, moreover, particularly characteristic of double entry-more characteristic perhaps than the ledger-because it so clearly expresses the inevitable duality which is concealed in all transactions. For this reason, undoubtedly, journalizing has always been a very important element in the teaching of double entry book- keeping, and in some countries it is a legal requirement that all transactions pass through the journal. This last probably is due to the desire to have the facts conveniently assembled for authentication rather than to any wish to give further emphasis to the importance of the journal.